Final move - Carwin, Richard; Giles, Chelsea; Koutrae, Jai; Cohen, JD; Willems, Steven (CineGear Productions, 2013)
When the Chess Piece Killer (the case that cost his daughter's life) appears and wants to finish the game. Nick has to play, and if he loses a piece, the killer slaughters the person whose name is on the piece. When he takes Nick's younger daughter, the game becomes much more personal. Nick and Ali struggle to stop the killer. As time runs out, Nick works out the link between the placement of the victims when they are killed, and their placement on the board. But can he rescue Lisa in time?